FULERENO E ÓXIDO DE GRAFENO FUNCIONALIZADOS INTERAGINDO COM QUIMIOTERÁPICOS: UM ESTUDO TEÓRICO - Balreira, Flávia Gonçalves (2020)
Breast cancer is the leading cause of death in women worldwide. Although important advances have been achieved, current therapeutic strategies remain limited by chemoresistance, which worsens the prognosis. The AC chemotherapy regimen, which is the use of doxorubicin (DOX) in conjunction with cyclophosphamide (CYP), is used in some types of breast cancer, but has limited application due to cardiotoxicity and suppression of the inume system. New nanotechnology approaches to cancer treatment promise to reduce side effects, allowing selective delivery of drugs to tumor tissues, increasing antitumor activity. Considering the benefits of nanomedicine in drug delivery, this work aimed to evaluate the interaction of the DOX and CYP molecules with graphene oxide (cGO) and functionalized fullerene (C60f). Calculations of first principles were made, based on the Theory of Functional Density, where the structural, energetic and electronic properties of these interactions were analyzed. The interactions were evaluated with the isolated molecules interacting with the nanostructures and afterwards their synergism interaction with the nanostructures was evaluated to see if they are good carriers of CYP and DOX. In the case of graphene oxide, we observed that there are chemical bonds between the molecules and this nanomaterial, which makes this system not interesting for the purpose of the work. The interactions of fullerene with chemotherapeutic agents, either individually or with synergism, occur via physical adsorption. These results are very promising, as there were no significant changes in the electronic properties after the interactions, allowing these drugs to be easily released in a specific location without changes in their properties.